(untitled) (Research, Society and Development, 2022)
COVID-19 is a relatively new infectious disease that had numerous victims spread around the world during the year 2020. The rates of complications and mortality from the disease are higher in people who already have comorbidities, one of the most discussed and known is Diabetes. Mellitus. This study aims to collect data from the Municipal Health Department of the city of Cascavel-PR of all patients who contracted SARS-CoV-2 and progressed to Severe Acute Respiratory Syndrome (SARS) in 2020, in order to compare the number of patients, average length of stay and mortality rate of two groups of patients who contracted the infection and diagnosed with SARS: one group with pre-existing diabetes and the other without the disease. For this, a quantitative methodology will be used, of the descriptive type, analyzing the data obtained and presenting them in graphs in an explanatory and descriptive way. The research pointed out as main results that adults, between 41-80 years old were the most affected by COVID-19, in addition to that patients who had diabetes had a higher incidence of death when hospitalized in ICUs, compared to those who did not diabetics.